Determining Poverty and Quality of Life in Slums of Varanasi City - Jha, Darshan Kumar; Harshwardhan, Rahul; Tripathi, V. K. (National Geographical Journal of India, 2022)
This paper is an attempt to re-imagine Varanasi from the slums of the city. The paper also attempts to determine the quality of life in slums of Varanasi city and present a spatial pattern of Quality of Life across different slums. To understand and analyse poverty at the micro level, 10 variables were chosen and detailed survey of 180 households has been conducted in six slums located in different parts of the city. Z-score of the variables has been calculated, and composite Z-score has been determined by adding them for every slum. Based on the Z -score, slums were grouped into three categories of Quality of life ( Moderate, Low, and Very Low). The study unfolds that there is another Varanasi, which is poor, unhygienic and lacks basic services. Besides, this city co-exists with its spiritual milieu and cultural mosaic of the city. The study reveals that low quality of life exists in the slums of Varanasi city, but it varies from one slum to another